Unveiling the diversification and dispersal of the Lewinskya firma complex (Orthotrichaceae, Bryophyta) across Africa and India - Lara, Francisco; Díaz San Román, Raúl; Fernández-Mazuecos, Mario; Calleja, Juan Antonio; Flagmeier, Maren; Mazimpaka, Vicente; Garilleti, Ricardo; Draper, Isabel (Frontiers in Plant Science, 2024)
Intercontinental disjunctions are one of the most attractive and interesting biogeographical patterns. Bryophytes often exhibit such distributions, which is partly explained by their great ability to disperse over long distances. However, such intercontinental ranges are sometimes a distorted reality caused by the existence of unnoticed species. This study investigates whether the disjunction between East Africa and southern India of the moss Lewinskya firma reflects the genuine distribution of a single species or implies pseudo-cryptic species (whose morphological differentiation is subtle and have therefore been masked). An integrative taxonomic approach combining morphological and molecular methods (genotyping by sequencing, GBS) was used, based on a representation of samples specifically collected from all the major mountainous regions where this moss occurs. Two species, L. firma s. str. and L. afroindica sp. nov. are involved, whose ranges completely overlap in East Africa, although genetic distance and morphological differences in leaf apex shape, vaginula hairs shape and papillosity, spore ornamentation and peristome constitution and ornamentation allow distinguishing both. In addition, the range of L. afroindica extends into both southern Africa and southern India. The phylogenetic reconstruction obtained shows a certain degree of differentiation of the Indian populations, although they are yet morphologically indistinguishable from African populations. The results thus highlight both the existence of overlooked species and the complexity of bryophyte biogeography.